CD4 cell counts, complete blood picture and lipid profile in HIV infected and AIDS patients in a specific populace from South India - MVR Ratnam; Abhishek S Nayyar; B Kalivara Prasad; SVN Sashikiran; G Upendra; Debasis Sahu (The Egyptian Journal of Internal Medicine, 2017)
Context AIDS is caused by a retrovirus known as HIV which breaks down the body’s immune system leaving the patient vulnerable to a host of life-threatening opportunistic infections, neurological disorders, or unusual malignancies. According to estimates by WHO and UNAIDS, 35 million people were living with HIV globally at the end of the year 2013. The first AIDS case in India was detected in the year 1986. Seldom studies have been conducted correlating these parameters in the Indian population. Aim The present study was carried out to evaluate the CD4 cell counts, complete blood picture, and lipid profile in HIV-infected patients and those with AIDS and correlate these parameters with those obtained in the sero-negative controls. Materials and methods This was a cross-sectional, hospital-based study. The included participants were divided into three groups: group A consisted of 500 patients who were without any systemic illness as healthy controls, group B consisted of 500 patients who were diagnosed as having HIV infection, and group C consisted of 500 patients diagnosed as having AIDS depending on their CD4 cell counts. Permission from the Ethical Committee of the Institution as well as Superintendent of Government Hospital was taken to conduct the study. Evaluation of CD4 cell counts in patients with HIV infection and AIDS was done using CyFlow counter, whereas complete blood picture, hemoglobin (Hb), packed cell volume, red blood cell and white blood cells (WBCs) and platelet counts, were analyzed using Sysmex XP 100, a compact, fully automated analyzer. Lipid profile was evaluated using an automated analyzer, Erba EM 360 powered by a diffraction grating photometer. Results The results were found to be statistically significant, with the P-value being less than 0.001, for the CD4 cell counts, Hb, WBCs, and platelet counts. The levels of total cholesterol and low-density lipoproteins (LDLs) were significantly decreased whereas triglycerides and very LDLs were significantly increased in patients with AIDS when compared with the control group and patients with HIV infection. Conclusion CD4 cell counts, Hb, WBCs and platelet counts as well as total cholesterol, LDLs, triglycerides and very LDLs were significantly altered in patients with HIV infection and those with AIDS when compared with the controls.